Analisis Fraud Pentagon Terhadap Kecurangan Laporan Keuangan (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2021) - Ulfa Nur Diana Kamalia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study examines the effect of financial targets, nature of the industry, change in auditor, change of directors, and frequent number’s of CEO on fraudulent financial reporting. The populationHused is a manufacturing companyIthat has been listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. The data collection technique used in this study used a purposive sampling method with a sample of 65 companies. Data analysis method used in this study were descriptive statistical analysis and logistic regression analysis using SPSS 21. The results of this study indicate that financial targets have a significant positife effect on fraudulent financial statements. Nature of the industry and change of directors don’t have a significant positife effect on fraudulent financial statements. changes in auditors and frequent number’s of CEO don’t have a significant negative effect on fraudulent financial statements. Keyword : fraud pentagon, fraudulent financial statements